2015
DOI: 10.3109/09553002.2014.980467
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effects of low-intensity extremely high-frequency electromagnetic radiation on content and composition of fatty acids in thymus of mice exposed to X-rays

Abstract: Changes in the content and composition of PUFA in the early period after treatments as well as at the restoration of the thymus weight under the combined action of EHF EMR and X-rays indicate to an active participation of FA in the acceleration of post-radiation recovery of the thymus by EHF EMR exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Thymus and spleen are the most important hematopoietic organs. Our data showed that thymus and spleen index was reduced after irradiation ( p < 0.05), which is consistent with other reports [ 18 , 19 ]. The thymus index at seven and 14 days after irradiation and the spleen index at 14 days after irradiation were increased by L. ruthenicum ( p < 0.05) .…”
Section: Discussionsupporting
confidence: 93%
“…Thymus and spleen are the most important hematopoietic organs. Our data showed that thymus and spleen index was reduced after irradiation ( p < 0.05), which is consistent with other reports [ 18 , 19 ]. The thymus index at seven and 14 days after irradiation and the spleen index at 14 days after irradiation were increased by L. ruthenicum ( p < 0.05) .…”
Section: Discussionsupporting
confidence: 93%
“…The frequency used in that experiment was similar to the one we used, although power density was almost 10-fold higher, and this difference alone might have affected the results. Some positive results have been obtained when 42.2-GHz millimeter waves were used on murine cells or mice in in vivo experiments [2732]. However, these experiments used conditions totally different from ours.…”
Section: Discussionmentioning
confidence: 91%
“…The authors also examined the effect of exposure to X-rays of healthy mice, which was reported to reduce the total weight of the thymus. However, when the thymus was exposed to MMWs before or after exposure to X-rays, the fatty acid content was restored and was no longer significantly different from controls [112]. Overall, the authors reported a potential protective effect of MMWs on the recovery of fatty acids, however, all the results came from the same research group with a lack of replication from others.…”
Section: Other Effectsmentioning
confidence: 87%
“…The effect on fatty acid composition in mice exposed to MMWs has been examined by a Russian research group using a number of experimental methods [110][111][112]. One study that exposed mice afflicted with an inflammatory condition to low-level MMWs reported no change in the fatty acid concentrations in the blood plasma.…”
Section: Other Effectsmentioning
confidence: 99%